Ageing Organizations: Reviewing the Literature and Making a Few Recommendations for Human Resource Management - Salomao Filho, Alfredo; Tillmanns, Tanja; Corrigan, Trudy (Merits, 2023)
In an ageing society, organizations must consider the inclusion and effective management of older professionals if they wish to remain competitive. Besides having harmful and far-reaching effects on people’s health, age discrimination in the workplace leads to absenteeism, lower levels of productivity, and early retirement. Within such a context, this problematic organizational feature of most Western, now ageing, organizations and labour markets starts gaining more relevance. However, to date there has been little discussion, research, or policy development to ensure that older employees’ skills and capabilities are optimally put to use by organizations without the occurrence of ageism. We present the results of a systematic literature review based on 30 studies in the context of ageing organizations to make recommendations for human resource management. We suggest an approach to effectively manage intergenerational organizations, reducing the occurrence of age discrimination and its related consequences, as well as to achieve high employee engagement. Our review indicates that a strong ethics framework that is continuously followed, disseminated, and updated by management, together with a combination of efforts from all stakeholders, may accomplish the best results towards a culture that respects and values people of all ages at work, positively impacting on productivit
Keywords: human resources management; ageing organizations; older employees; organizational policy; recruitment and training; intergenerational; ageism

Design Criteria for Visual Cues: Triggering Emotions to Stimulate the Process of Ethics and Value Clarification - Tillmanns, Tanja; Holland, Charlotte; Salomao Filho, Alfredo; et al. (Education Studies Association of Ireland Annual Conference, 2018)

Design Criteria for Visual Cues Used in Disruptive Learning Interventions Within Sustainability Education - Holland, Charlotte; Salomão Filho, Alfredo; Tillmanns, Tanja (Discourse and Communication for Sustainable Education, 2017)
This paper presents the design criteria for Visual Cues – visual stimuli that are used in combination with other pedagogical processes and tools in Disruptive Learning interventions in sustainability education – to disrupt learners’ existing frames of mind and help re-orient learners’ mind-sets towards sustainability. The theory of Disruptive Learning rests on the premise that if learners’ frames of mind or frames of reference can be disrupted (in other words, challenged), then learners’ mind-sets can be re-oriented towards sustainability, and indeed learners can be motivated to engage in change agency for sustainability. The use of Visual Cues thus unsettle or challenge learners’ mind-sets, and in doing so, set them on the pathway towards re-orientation in becoming more sustainability oriented, and/or in motivating engagement in sustainability change agency. The findings form part of a broader research study on ESD conducted in a higher education institution in Ireland within an undergraduate degree of teacher education. Kathy Charmaz’ Constructivist Grounded Theory approach guided the entire study, resulting in the articulation of the theory of, and processes within, Disruptive Learning. This paper presents design criteria for Visual Cues that were articulated through a thematic analysis approach from data emerging from reflective diaries, follow-up interviews, audio recordings and observational notes. The findings from this study in respect of design criteria state that Visual Cues must disrupt rather than disturb; must represent (have impressions of) real life contexts, scenarios, practices or events; must provoke controversy; must contain a visual stimulation; and can have a critical question.<br
Keywords: Disruptive Learning; Visual Cue; pedagogy; sustainability education; higher education

Digital Inclusion and Lifelong Learning via Smart Home Technology: the Irish case - Salomao Filho, Alfredo; Corrigan, Trudy; Tillmanns, Tanja (Education Studies Association of Ireland Annual Conference, 2022)

Exploring the potential of AI in educational media production - Tillmanns, Tanja; Salomao Filho, Alfredo (Media & Learning Association, 2023)

Innovating Media and Learning in Higher Education with EU Support - Tillmanns, Tanja; Salomao Filho, Alfredo; Hetzner, Sonia (Back to the Future?, 2024)

Mapping Tomorrow’s Teaching and Learning Spaces: A Systematic Review on GenAI in Higher Education - Tillmanns, Tanja; Salomao Filho, Alfredo; Rudra, Susmita; Weber, Peter; Dawitz, Julia; Wiersma, Emma; Dudenaite, Dovile; Reynolds, Sally (Trends in Higher Education, 2025)
This collective systematic literature review is part of an Erasmus+ project, “TaLAI: Teaching and Learning with AI in Higher Education”. The review investigates the current state of Generative Artificial Intelligence (GenAI) in higher education, aiming to inform curriculum design and further developments within digital education. Employing a descriptive, textual narrative synthesis approach, the study analysed literature across four thematic areas: learning objectives, teaching and learning activities, curriculum development, and institutional support for ethical and responsible GenAI use. The review analysed 93 peer-reviewed articles from eight databases using a keyword-based search strategy, a collaborative coding process involving multiple researchers, in vivo coding and transparent documentation. The findings provide an overview of recommendations for integrating GenAI into teaching and learning, contributing to the development of effective and ethical AI-enhanced learning environments in higher education. The literature reveals consensus on the importance of incorporating GenAI into higher education. Common themes like mentorship, personalised learning, creativity, emotional intelligence, and higher-order thinking highlight the persistent need to align human-centred educational practices with the capabilities of GenAI technologie
Keywords: generative artificial intelligence; higher education; academic integrity; guidelines; AI literacy

Non-human Agency in International Students’ Learning Realities: A Choreography of Actor-Network Theory and Rhizomes - Salomao Filho, Alfredo; Tillmanns, Tanja (Rhizome Metaphor, 2023)
This chapter explores international students’ informal learning experiences through the lenses of Deleuze & Guatarri’s rhizome philosophy and Actor-Network Theory (ANT). Reflections upon the principles of the rhizome as well as ANT ontologically symmetrical materialism are examined in light of empirical data. This analytical effort seeks to illuminate how learning is non-linearly negotiated by a series of surprising actors, coming into being as an effect of a non-essentialist set of relations. Focusing on theoretical affinity rather than divergence, the creative dialogue established between ANT and the rhizome philosophy gives space for a “choreography” of learning as a relational performance, which is enacted through international students’ practices, and objects that shift from being seemingly irrelevant to becoming matters of controversy.<br
Keywords: Postqualitative learning; Actor-network theory; Rhizome; Non-human agency; Education

Power Ageing: Addressing Ageism in the Workplace - Salomao Filho, Alfredo; Tillmanns, Tanja; Corrigan, Trudy (Dublin City University and Irish Research Council "New Horizons Awards", 2022)

Power Ageing: Addressing Ageism in the Workplace Report - Salomao Filho, Alfredo; Tillmanns, Tanja; Corrigan, Trudy (2022)

Reflecting on Partnerships of Sustainability Learning: Enacting a Lewin–Deleuze–Guattari Rhizome - Tillmanns, Tanja; Salomão Filho, Alfredo (Sustainability, 2020)
This paper works towards the enactment of a Lewin–Deleuze–Guattari rhizome. We assemble Deleuze and Guattari’s principles of the rhizome, Lewin’s idea of re-education, and reflections on the performance of one of the authors in the lecture hall, bringing into being what could be a rhizomatic partnership approach to sustainability learning in a higher education setting. The reflections are based on experiences delivering a sustainability module within a business education context, mainly for international students in Germany. The purpose of this paper is to illuminate possibilities of student–teacher partnership assemblages, aiming to motivate sustainability change agency on “people-yet-to-come”: those who are open to enacting difference, or multifaceted, heterogeneous, and often partial transformations addressing the current plethora of contemporary crises.<br
Keywords: rhizome; transformation; sustainability education; teacher–student partnership; change agency

Reflecting on Partnerships of Sustainability Learning: Enacting a Lewin-Deleuze-Guattari Rhizome (reprint) - Tillmanns, Tanja; Salomao Filho, Alfredo (Prime Archives in Sustainability, 2021)

SmartYourHome in Ireland - Salomao Filho, Alfredo; Corrigan, Trudy; Tillmanns, Tanja (Dublin City University EU Erasmus + Conference, 2020)

Towards Digital Inclusion in Europe: designing a course on smart home technology for older adults - Salomao Filho, Alfredo; Corrigan, Trudy; Tillmanns, Tanja (The Online Journal of New Horizons in Education, 2021)

Use and Perception of Generative AI in Higher Education: Insights from the ERASMUS+ Project 'Teaching and Learning with Artificial Intelligence' (TaLAI) - Rudra, Susmita; Weber, Peter; Tillmanns, Tanja; Salomao Filho, Alfredo; Wiersma, Emma; Dawitz, Julia; Dudenaite, Dovile; Reynolds, Sally (Proceedings of the 17th International Conference on Computer Supported Education - Volume 2: CSEDU,, 2025)
The integration of Generative Artificial Intelligence (GenAI) in higher education offers transformative opportunities alongside significant challenges for both educators and students. This study, part of the ERASMUS+ project Teaching and Learning with Artificial Intelligence (TaLAI), aims to explore the familiarity, usage patterns, and perceptions of GenAI in academic settings. A survey of 152 students (mainly from Germany, Belgium, and the Netherlands) and 118 educators (81 professors, 37 trainers) reveals widespread GenAI use, with ChatGPT being the most common tool. Findings indicate both enthusiasm for GenAI’s potential benefits and concerns regarding ethical implications, academic integrity, and its impact on learning processes. While students and educators recognize GenAI’s ability to enhance learning and productivity, uncertainties persist regarding assessment practices and its potential short and long-term effects on various aspect such as decision making, creativity, and mem ory performance. The study also highlights gaps in institutional support and policy, emphasizing the need for clearer communication to ensure responsible AI adoption. This paper contributes to the ongoing discussions on GenAI in higher education and is aimed at educators, policymakers, and researchers concerned with its responsible use. By addressing students’ and educators' both perspectives and concerns, institutions and policymakers can develop well-informed strategies and guidelines that promote responsible and effective use of GenAI, ultimately enhancing the overall teaching and learning experience in academic environment
Keywords: Generative AI; Higher Education; Perception; Survey Results